A hybrid method for computing the effective properties of composites containing arbitrarily shaped inclusions. (1st April 2015) - Srinivasulu, G.; Velmurugan, R.; Jayasankar, S.
Highlights: A hybrid method for composites with arbitrarily shaped inclusions is developed. Hybrid method is more efficient than the pure finite element based approach. Influence of inclusion shape on the effective properties of composites is studied. Inclusion shape has a significant influence on the effective properties. Composites with fibers of non-circular cross sections have better performance. Abstract: A novel hybrid method is developed to compute the effective properties of composites containing arbitrarily shaped inclusions. In this method, finite element analysis of a single inclusion representative volume element model is used to compute the Eshelby tensor of the inclusion. This tensor is substituted into Mori–Tanaka model to compute the effective properties. Predictions by the hybrid method are compared with the predictions by a pure analytical method as well as a pure numerical method. Results indicate that the composites with triangular, rectangular and irregular section inclusions have significantly better effective properties than the corresponding composites with circular section inclusions.